Writing the Environmental History of the World's Largest State: Four Decades of Scholarship on Russia and the USSR. (1st January 2013) - Bonhomme, Brian
Abstract : This article surveys and analyzes long-term and recent trends in English-language scholarship on the environmental history of Russia and the USSR. This literature, following certain precursors, began to take shape in the early 1970s and was influenced partly by the rise of popular environmentalism in the West and also by the exigencies and context of the Cold War. Gorbachev-era liberal reforms and the subsequent collapse of the Soviet Union conditioned a new wave of writings beginning in the late 1980s that sought to nuance and complicate Cold War-era narratives. This second wave of historiography highlighted the existence of divergent and positive trends – including successful experiments with nature preserves in the early Soviet period. It also effectively challenged earlier notions of the Soviet Union as a monolithic state/culture with a relatively simple environmental history that could be inferred in part from an examination of Marxist-Leninist ideology. Post-Soviet scholarship (which can be considered a third wave) is more heterogeneous than either of its predecessors but overall continues the trend of replacing broad narratives and fondly-held assumptions with knowledge gained from detailed investigations, painstaking archival-based reconstructions, and – frequently – regional and local rather than national focuses. Although much interesting work continues to emerge, the field remains heavily skewed towards the Late-Imperial, Soviet, and post-Soviet periods, which seems an important shortcoming. Similarly, there is an abiding (if understandable) preoccupation with the role of political culture and systems, at the expense of alternative approaches, many of which have proven fruitful in the study of other geographical areas.